KETERLIBATAN MEDIA SOSIAL DALAM KEGIATAN KONSUMSI RUMAH TANGGA - Herispon, Herispon (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This study shows a comparison of the involvement of social media, social media tools, in household consumption activities using household units as respondents in several provincial and district cities in Indonesia. Using the convenience sampling method in sampling, and quantitative descriptive methods in the analysis. The findings, that the social media involvement of district city respondents is higher than provincial city respondents. As for the most used social media platforms; Provincial city respondents, namely; WhatsApp, Youtube, and Facebook, Regency city respondents, namely; Youtube, Google/web, and Telegram. The use of social media in consumption activities is the most, provincial city respondents for chatting, reading online news, and school/college info, district city respondents for ordering breakfast or food, for chatting, and reading online news.